"Twice as valuable as that of Eumorphopulos and twice as famous ..." (Vita Sackville-West, All Passion Spent, 1931) the real and imaginary world of the Chinese art collector - Pearce, Nick 1956- (2021)
The period between about 1900 and 1937 witnessed the opening up of an international market in Chinese artefacts at a time when China was vulnerable to encroachment and, after 1911 with the fall of the last imperial dynasty, was in political, social and economic turmoil. During the post-WW1 decades the visibility of the country and its cultural history also stimulated an academic and popular interest in Chinese material culture of all types and periods, but particularly burial objects being unearthed through railway construction (bronzes, jades and ceramics), which initiated both legal and illegal excavations and the market circulation of collections formerly owned by the Chinese élite. These opportunities to 'collect' ended only with the outbreak of the Sino-Japanese War in 1937, when access to China was severely curtailed. In this article, I will focus on the way in which the visibility of these collectors impacted upon popular culture of the inter-war period, particularly the novel. Referencing actual collectors against their fictional counterparts offers an intriguing insight into character, motivation and the market for Chinese works of art at the time. Indeed the eccentricity and flamboyance of a number of real collectors made them ideal material for the writers of fiction
Keywords: Geschichte 1900-1937; Kunstmarkt; Kunst; China; Europa; Japan